2021
DOI: 10.1111/een.13084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of succession between two Silphidae, Necrophila japonica and Nicrophorus concolor on small vertebrate carcasses

Abstract: 1. In carrion insect communities, facilitation and processing chain models, in which carcass feeding by early colonists facilitates colonisation by later colonists, have been regarded as the succession mechanisms without sufficient empirical evidence. Although the two models are similar, the processing chain model also assumes a facilitation process independent of early colonists. 2. To reveal the succession mechanisms, field experiments focusing on two silphids, Necrophila japonica, early colonist, and Nicrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…The abundance of emerging Staphylinidae peaked in the second and third sampling period when the abundance of other scavenger beetles decreased considerably. This pattern suggests that resource competition or predator–prey relationship between these beetles may contribute to the observed community dynamics in addition to habitat and resource preferences (see also Heard, 1994; Ito, 2021; Zanetti et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The abundance of emerging Staphylinidae peaked in the second and third sampling period when the abundance of other scavenger beetles decreased considerably. This pattern suggests that resource competition or predator–prey relationship between these beetles may contribute to the observed community dynamics in addition to habitat and resource preferences (see also Heard, 1994; Ito, 2021; Zanetti et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…This pattern suggests that resource competition or predator-prey relationship between these beetles may contribute to the observed community dynamics in addition to habitat and resource preferences (see also Heard, 1994;Ito, 2021;Zanetti et al, 2015).…”
Section: Carcass Effectsmentioning
confidence: 95%
“…Rather, the changing profile of microbially‐derived volatiles likely determines the succession of insects. Fly larvae and other carrion feeders have important indirect effects on the volatile profile as their activity opens holes through the skin where microbes can proliferate (Brodie et al, 2016; Ito, 2022; Putnam, 1978), leading to the release of greater quantities of attractants (Chen et al, 2020; Recinos‐Aguilar et al, 2019). When burying beetle parents prepare a carcass during nest‐making, they alter the microbial community and repair any such holes to better hide their resource from competitors (Duarte et al, 2018; Trumbo, 2017; Trumbo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study has revealed interspecific interactions between the Silphini beetle, Necrophila japonica, and Nicrophorus concolor on small carcasses (Ito, 2022). In this study, carcasses fed on by Ne.…”
Section: Introductionmentioning
confidence: 89%
“…Flies and Silphini beetles (Staphylinidae, Silphinae) are considered the main colonists that interact on large carcasses (Anderson, 1982 ; Matuszewski & MĄdra‐Bielewicz, 2022 ), and Nicrophorus beetles (Staphylinidae, Silphinae, Nicrophorini) interact on small carcasses (Anderson, 1982 ; Trumbo & Bloch, 2002 ). However, a recent study has revealed interspecific interactions between the Silphini beetle, Necrophila japonica , and Nicrophorus concolor on small carcasses (Ito, 2022 ). In this study, carcasses fed on by Ne.…”
Section: Introductionmentioning
confidence: 99%